Reducible appendiceal intussusception: A case report and review - Abdulrasool Alaee (Mazandaran University of Medical Sciences, 2012)
Appendiceal intussusception is a very rare cause of abdominal colic in childhood. This paper reports a reducible appendiceal intussusception in Article history: the barium enema in a girl and reviews articles in PubMed